ChemInform Abstract: Two New Triterpene Saponins from Acanthophyllum laxiusculum. Issue 41 (October 2015) - Pertuit, David; Baghery Lotfabad, Tayebe; Mitaine‐Offer, Anne‐Claire; Miyamoto, Tomofumi; Tanaka, Chiaki; Lacaille‐Dubois, Marie‐Aleth
Abstract isolation and structure determination